Plasma modeling : methods and applications - Colonna, Gianpiero; D'Angola, Antonio (IOP (Series). Release 3., 2016)
Plasma Modeling: Methods and Applications presents and discusses the different approaches that can be adopted for plasma modeling, giving details about theoretical and numerical methods. The book is intended to assist and direct students and researchers, who want to develop research activity in the field of plasma physics, in the choice of the best model for the problem of interest. The book is organised in three parts. The first describes kinetic models used in plasma investigations, consisting of the solution of the Boltzmann equation using different approaches. The second part develops the theory of fluid equations and of hybrid models, and the third part is devoted to applications, considering some practical problems of interest in different fields.